What motivates members to transact on social C2C communities? A theoretical explanation. Issue 4 (20th February 2020) - Trehan, Deepak; Sharma, Rajat
Abstract : Purpose: This paper aims to investigate the consumer motivation to buy products on consumer-to-consumer (C2C) communities on social networking sites (SNSs). These transactions involve no intermediation or payment of fees by any party. The phenomenon is in contrast with the traditional C2C transactions, on websites such as eBay, where the company website facilitates the transaction between consumers, charges a fee to sellers and provides limited information about buyers and sellers. Design/methodology/approach: Drawing from media richness theory and social capital theory, this paper thus proposes and empirically tests a theoretical model developed using data collected from people making transactions on these communities that synthesize the motivations behind consumers' intention to buy. Findings: The results indicate that the media richness of the Facebook platform increases the social capital and sense of virtual community among users, which further impacts the purchase intentions of users. Social capital alone does not lead to purchase intention and indirectly impacts purchase intentions through the trust dimension. Research limitations/implications: This study contributes to theorizing the role of the platform, social capital and sense of virtual community in buying behavior on SNSs and provides valuable new insights into these constructs for the brand managers on social media sites. Originality/value: Existing research on social commerce does not hold true for C2C communities on SNSs. This paper provides a new perspective into these communities through the lens of media richness and social capital constructs as antecedents of purchase intentions on these communities.